THE MOLECULAR APPROACH REVEALS THE RELATIONSHIP AMONG VENUS CLAMS ( Meretrix spp.) COMMUNITY IN MALAYSIA - Mohd Hanafi Idris; Abu Hena Mustafa Kamal; Hadi Hamli; Amy Rajaee; Abdulla Al-Asif (SEAMEO BIOTROP, 2022)
Molecular study is important to detect variations and similarities among species from the same genus, in case if they do not encompass any morphological or physiological differences. The study was conducted to differentiate among species of Meretrix spp. (Meretrix lyrata, M. meretrix, and M. lusoria) obtained from two locations in Malaysia through the phylogenetic tree. The adductor muscle tissues were used to extract DNA and to perform other procedures; the samples were subjected to analyses using PCR and gel electrophoresis. The multiple sequence comparison was conducted by MUSCLE and the phylogenetic relationships were established using Maximum Likelihood (ML) statistical methods with MEGA 6.0 statistical software. M. lyrata samples showed 99% similarity to the three accessions sequence, where M. lyrata indicated 87% similarities, and M. meretrix showed not more than 89% similarities from the deposited sequence. The nucleotide base composition sequences consisted of the mean of Thiamine (T) 37.9%, Cytosine (C) 15.4%, Adenine (A) 27.4%, and Guanine (G) 19.4%. Maximum Likelihood (ML) analysis was conducted using the Tamura 3-parameter model to establish five major clades on Meretrix spp. and two out-groups clades significantly different from the Meretrix spp. These major clades were closely related to each other at the 50% evidence of bootstrap, which grouped as genus Meretrix. The present study on Meretrix spp. from the Sarawak locality was able to differentiate COI sequences between M. lyrata, M. meretrix, and M. lusoria. M. lusoria was close related to M. meretrix with strong bootstrap supporting evidence at 96% scoring. Moreover, M. lyrata was inferred as the ancestor to M. meretrix, and M. lusoria from Sarawak, Malaysia.